Qualidade de sementes de milho híbrido tratadas com inseticidas, armazenadas em duas condições de ambiente - Tonin, Rosane Fátima Baldiga (2008)
The treatment of seeds is a practice widely disseminated in the Brazilian agricultural areas, which, linked to other cultural practices, has contributed to the increase in productivity, costs reduction, final product improvement, reduction of damage to the environment and also offers a good protection for seeds, in the field level as well as in storage. The objective of this paper is to check the effect of the seed treatment of three maize hybrids on seedling emergence (stand), performance in storage, germination and seed vigor. The seeds were treated with three insecticides: Insecticide one (Thiametoxan - Cruiser 350 FS ® ); Insecticide two (Neonicotinóide) and Insecticide three [Neonicotinóide+(Imidaclopride+Thiodicarbe)], with 60,000 seed per 120ml of insecticide. After being treated, the seeds were stored for a period of 270 days, in two environments. One with (10°C) temperature control and relative humidity (60%) and the other one under normal conditions of storage. During this period, 45 in 45 days evaluations were accomplished, through germination and vigor tests. In addition to germination and cooling tests, sanitation analysis, seedling emergency and seed inoculation was carried out. The results obtained allow concluding that the maintenance of quality seeds of hybrid maize, treated with insecticides, depend on the hybrid and chemical product used in their treatment and that the reduction in feasibility and vigor of seeds treated with thiametoxan (Cruiser 350 FS ® ) is intensified due to the storage period extension.